Agriculture water management, food security, and sustainable agriculture in the People's Republic of China and India under climate change - Jeetendra Prakash Aryal; Dil Bahadur Rahut; Augusto Becerra López-Lavalle; Tetsushi Sonobe (Asian Development Bank Institute (ADBI), 2024)
Water shortage is one of the major environmental challenges in emerging Asian economies such as India and the People's Republic of China (PRC), presenting significant threats to livelihood and food security in coming decades. The growing population, increasing demand for food, rapid urbanization, and climate-induced water stress will make water an increasingly scarce and critical resource in these nations. Agriculture, as the largest water-consuming sector, accounts for 64% of water use in the PRC and 80% in India. Understanding both the demand and supply sides of water management in agriculture is crucial to addressing future water and food security in these countries. While there are significant differences between the PRC and India in agricultural water management, both countries have predominantly focused on supply-side measures, emphasizing sustainable production practices such as "more crop per drop". To manage agricultural water resources effectively and ensure long-term sustainability, it is essential to adopt a broader perspective that integrates a comprehensive food system and natural resource management approach. This holistic view will help in developing strategies that balance both the supply and demand sides of water management, addressing the complex challenges of water scarcity in India and the PRC.
Keywords: Q25; Q50; 330; agricultural water management; food security; sustainable agriculture; India; People's Republic of China